A comprehensive phylogenetic analysis of coelacanth fishes (Sarcopterygii, Actinistia) with comments on the composition of the Mawsoniidae and Latimeriidae: evaluating old and new methodological challenges and constraints. (2nd December 2021) - Toriño, Pablo; Soto, Matías; Perea, Daniel
ABSTRACT: The phylogeny of coelacanths (Devonian-Recent) has been a matter of discussion at least since 1940s following the discovery of Latimeria chalumnae, and it remains as a revisited issue in most recent works. In this contribution, an updated phylogenetic analysis based on a new consensual data matrix is presented, merging most of the emendations proposed over the past two decades, and including a completely reviewed character scoring for some genera. Also, a complete Stratigraphic Tree Analysis is introduced, calibrating divergence times, branch lengths, potential ghost ranges and quantifying the stratigraphic fit of the trees. The topologies are congruent with previous analyses, with exceptions: Mawsoniidae and Latimeriidae include some genera previously not considered as such. Implied weights analysis indicates that this result is influenced by homoplasies. Time-scaled phylogenies show a great proportion of cladogenetic events concentrated in the Permian-Triassic transition, leading to the diversification of the Mesozoic modern stock of the group (Latimerioidei). In spite of some large ghost ranges ( e.g. Latimeria, ranging from Middle-Upper Jurassic), the metrics indicate relatively good stratigraphic fits. Although additional reviews of both the character codings and the scorings of several taxa are still needed, these preliminary results can constitute an input for future macroevolutionary studies.